Plasma micronutrient status is improved after a 3-month dietary intervention with 5 daily portions of fruits and vegetables: implications for optimal antioxidant levels - Sies Helmut; Verde Pablo E; Carrillo Juan-Carlos; Polidori Maria; Siegrist Johannes; Stahl Wilhelm (Nutrition Journal, 2009)
Abstract To explore the effects of increasing fruit and vegetable intake and the resulting effects on levels of circulating micronutrients in a community-dwelling population with an already high consumption of fruits and vegetables, 112 volunteers (86% women) underwent targeted dietary counseling for three months. At the beginning of the study and after 4, 8 and 12 weeks a food frequency questionnaire was filled in, and plasma levels of dietary antioxidants as well as biomarkers of oxidative lipid and protein damage were determined. Compared to baseline, especially the intake of fruits was significantly improved after 3 months of intervention, and mean plasma levels of lutein, zeaxanthin, β-cryptoxanthin, lycopene, α- and β-carotene, retinol, α-tocopherol, vitamin C and vitamin B6 were increased. Biomarkers of oxidative stress remained unchanged. Thus, a nutritional counseling program is capable of improving plasma levels of antioxidants even in a health-conscious population. A decrease in biomarkers of oxidative stress, however, does not occur.